Atom Probe Tomography Characterization of Dopant Distributions in Si FinFET: Challenges and Solutions. (February 2020) - Hu, Rong; Xue, Jing; Wu, Xingping; Zhang, Yanbo; Zhu, Huilong; Sha, Gang
Abstract: Atom probe tomography (APT) has emerged as an important tool in characterizing three-dimensional semiconductor devices. However, the complex structure and hybrid nature of a semiconductor device can pose serious challenges to the accurate measurement of dopants. In particular, local magnification and trajectory aberration observed when analyzing hybrid materials with different evaporation fields can cause severe distortions in reconstructed geometry and uncertainty in local chemistry measurement. To address these challenges, this study systematically investigates the effect of APT sampling directions on the measurement of n-type dopants P and As in an Si fin field-effect transistor (FinFET). We demonstrate that the APT samples made with their Z -axis perpendicular to the center axis of the fin are effective to minimize the negative effects that result from evaporation field differences between the Si fin and SiO2 on reconstruction and achieve improved measurement of dopant distributions. In addition, new insights have been gained regarding the distribution of ion-implanted P and As in the Si FinFET.